Mechanism of progesterone neuroprotection of rat cerebellar Purkinje cells following oxygen–glucose deprivation - Ardeshiri, A. (2006)
The survival of rat Purkinje cell (PCs) cerebellar cultures was used to test the hypothesis that progesterone is protective againstoxygen–glucose deprivation through potentiation of GABA(A) receptor activity. Electrophysiological recordings confirm that PCs develop robust excitatory and inhibitory synapses in culture. Exposure of cultured PCs to increasing concentrations of progesterone during oxygen–glucose deprivation revealed a concentration-dependent protection by progesterone, with significant protection observed at physiological concentrations, as low as 10 nm. The concurrent application of the GABA(A) receptor antagonist picrotoxin (100 µm) completely abolished the neuroprotection afforded by progesterone, indicating that progesterone is neuroprotective through activation of GABA(A) receptors. Progesterone potentiates GABA(A) receptor activity indirectly through its metabolites, such as allopregnanolone (ALLO). Therefore, ALLO was applied to PC cultures and was observed to produce significant protection at all concentrations tested, from 10 to 1000 nm. Finally, the inhibition of progesterone metabolism with finasteride abolished the protection afforded by progesterone without having any effect on the neuroprotection caused by ALLO. These data indicate that progesterone protects cerebellar PCs at physiological concentrations through a GABA-active metabolite.